Two anomalous new species of Rhagovelia (Heteroptera: Veliidae) from southern New Guinea - Polhemus, Dan A. (Zootaxa, 2024)
Two new species of Rhagovelia are described from southern New Guinea: R. kiunga from the Fly River basin of Papua New Guinea, and R. timikana from the Iweka River basin of Indonesian New Guinea. These species are placed in a newly defined R. kiunga species group on the basis of shared distinctive morphological character states. Photographic figures of the dorsal habitus in both sexes and other key morphological characters are provided for both species, along with line drawings of the male parameres and a distribution map.